Ovarian endometriosis and fertility preservation problem - Galina E. Chernukha; Madina R. Dumanovskaya; Lilia M. Ilina (IP Berlin A.V., 2021)
Aim. To review the most recent literature regarding the modern management of women with ovarian endometriosis and no desire for immediate pregnancy but wanted fertility preservation in future. Materials and methods. The analysis of latest publications on this topic has been carried out. Results. Ovarian endometriosis is associated with infertility due to several factors including potential gonadotoxic effect per se and ovarian reserve decline after surgical treatment. Medical treatment is the first-line therapeutic option for patients with pelvic pain and no desire for immediate pregnancy in absence indications for the urgent surgery, for prevention disease progression. Postoperative long-term medical therapy has been effective in the prevention of endometrioma recurrence, repeated surgery, additional ovarian reserve decline and preserve fertility in future. Conclusion. Ovarian endometriosis management should be individualized according to the patients intentions and priorities. Long-term progestins most appropriate therapy for fertility preservation in women prior to performing surgery or provide assisted reproductive technologies, if needed.